2015
DOI: 10.1177/0309364614535232
|View full text |Cite
|
Sign up to set email alerts
|

An engineering-based approach for design and fabrication of a customized nasal prosthesis

Abstract: Custom-made nasal prostheses with minimum contact and discomfort for the patient can be achieved using an engineering approach based on digital technologies and additive manufacturing that is cost-effective and less time-consuming than the manual procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
(25 reference statements)
0
15
0
1
Order By: Relevance
“…Furthermore, 238 studies were screened according to the inclusion and exclusion criteria; therefore, an additional 217 studies were excluded based on their study design and rehabilitation techniques (craniofacial surgical reconstruction with titanium plates, mesh and ceramic implants, craniofacial prosthetic rehabilitation without digital solutions, prosthetic rehabilitation of intra-oral defects, and short communications without digital techniques). A total of 21 studies [9,19,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] involving 23 cases were planned and executed with digital planning software for prosthetic rehabilitation of nasal defects (Table 1). Due to the included studies' quality and data heterogeneity, meta-analysis could not be performed.…”
Section: Study Selectionmentioning
confidence: 99%
“…Furthermore, 238 studies were screened according to the inclusion and exclusion criteria; therefore, an additional 217 studies were excluded based on their study design and rehabilitation techniques (craniofacial surgical reconstruction with titanium plates, mesh and ceramic implants, craniofacial prosthetic rehabilitation without digital solutions, prosthetic rehabilitation of intra-oral defects, and short communications without digital techniques). A total of 21 studies [9,19,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] involving 23 cases were planned and executed with digital planning software for prosthetic rehabilitation of nasal defects (Table 1). Due to the included studies' quality and data heterogeneity, meta-analysis could not be performed.…”
Section: Study Selectionmentioning
confidence: 99%
“…Recent studies have shown that dental prostheses manufactured using the AM method have an acceptable degree of precision compared to prostheses made using the SM and CV methods [ 1 , 8 ]. Furthermore, several studies have reported the application of AM in maxillofacial reconstruction [ 4 , 9 , 10 , 11 , 12 ], implant fixture construction and intervention [ 13 , 14 ], orthodontic appliances [ 15 ], metal bridges [ 6 ], guided tissue regeneration [ 16 ], tissue surface [ 17 ], and clasps of removable partial dentures [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that dental prostheses manufactured using 3D printing method have an acceptable degree of precision compared with prostheses made using milling or conventional methods [ 7 ]. Furthermore, several studies have reported 3D printing applications in maxillofacial reconstruction [ 8 , 9 , 10 ], implant fixture construction and intervention [ 11 ], orthodontic appliances [ 12 ], metal bridges [ 13 ], guided tissue regeneration [ 14 ], tissue surfaces [ 15 ], and the metal frameworks of removable partial dentures [ 16 ]. The fabrication of dental provisional restorations is one remaining area that will benefit from these recent developments.…”
Section: Introductionmentioning
confidence: 99%